2023
DOI: 10.1001/jamapediatrics.2022.3828
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Non–English-Speaking Participants in Pediatric Health Research

Abstract: ImportanceThe inclusion of non–English-speaking (NES) participants in pediatric research is an essential step to improving health equity for these populations. Although some studies have shown lack of progress in NES research participation in the past decade, few have examined NES inclusivity in pediatric research or details about the practices that researchers have used to communicate with NES participants.ObjectiveTo assess how frequently NES families were included in pediatric research, how rates of inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…13 In the United States, research often excludes non-English-speaking patients, as demonstrated in a recent study of 5008 pediatric research articles that found only 9% included non-English speakers. 22 This common exclusion makes it difficult to assess outcomes and disparities in care affecting this population.…”
Section: Discussionmentioning
confidence: 99%
“…13 In the United States, research often excludes non-English-speaking patients, as demonstrated in a recent study of 5008 pediatric research articles that found only 9% included non-English speakers. 22 This common exclusion makes it difficult to assess outcomes and disparities in care affecting this population.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies on equity and inclusion in medical education, training, access and research may easily support our hypothesis that there is not enough equity on this issue. Participation in clinical trials is historically imbalanced according to ethnicity [ 16 , 17 , 18 , 19 , 20 ], access in medical education [ 19 , 21 ] and access to care and diagnostics [ 21 , 22 , 23 , 24 , 25 , 26 ]. More specifically regarding paediatric dermatological conditions, it is well discussed the issue of the late recognition of jaundice in Black newborns and the disproportionate impact of kernicterus on this population [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…These preferences align closely with the findings of Ford, et al [30] who reported on the importance of having Spanish-speaking personnel available to assist with the recruitment of Hispanic participants. In addition to language barriers of participants, Chen, et al [31] reported that despite the federal mandates to include minority groups in research studies, principal investigators are less likely to include participants that do not speak English as their primary language in research studies. In a study conducted by Benavides-Vaello, [32], a significant number of participants expressed concerns about their legal status, leading to misconceptions regarding research participation and immigration.…”
Section: /9mentioning
confidence: 99%